Research and design of V-shaped deep trench sugarcane cultivating machine - LÜ Meiqiao; LIU Limin; WU Yu (浙江大学学报. 农业与生命科学版, 2019)
According to the agricultural characteristics of sugarcane planting in central Zhejiang Province, i.e. intertilling, fertilizing, ridging and earthing-up, the V-shaped deep trench sugarcane cultivator is equipped with good working parts, such as soil digging, breaking, casting and trench clearing. It can form a good V-shaped groove cross section. This paper analyzed the agronomic requirements of sugarcane planting in central Zhejiang Province and narrow row spacing, designing the key parts of the whole machine, such as V-shaped deep trench ridging cutter plate, trench clearing, etc. Field experiment results showed that the efficiency of the management machine could reach 0.19 hm2/h. The trench depth and the thickness of soil could reach 230 mm on average and 70 mm, respectively. The trench depth stability coefficient reached about 85%. The soil breaking rate reached about 95%. The fertilizer distributor had a good effect on granular fertilizer. No obvious damage and seedling emergence were found in sugarcane seedlings. The design of the machine meets the agronomic requirements of sugarcane planting in central Zhejiang Province.